Treatment of Cardiovascular Dysfunction with PDE3-Inhibitors in Moderate and Severe Hypothermia—Effects on Cellular Elimination of Cyclic Adenosine Monophosphate and Cyclic Guanosine Monophosphate - Kuzmiszyn, Adrina Kalasho; Selli, Anders Lund; Smaglyukova, Natalia; Kondratiev, Timofei; Fuskevåg, Ole-Martin; Lyså, Roy Andre; Ravna, Aina Westrheim; Tveita, Torkjel; Sager, Georg; Dietrichs, Erik Sveberg (Frontiers in Physiology, 2022)
Introduction Rewarming from accidental hypothermia is often complicated by hypothermia-induced cardiovascular dysfunction, which could lead to shock. Current guidelines do not recommend any pharmacological treatment at core temperatures below 30°C, due to lack of knowledge. However, previous in vivo studies have shown promising results when using phosphodiesterase 3 (PDE3) inhibitors, which possess the combined effects of supporting cardiac function and alleviating the peripheral vascular resistance through changes in cyclic nucleotide levels. This study therefore aims to investigate whether PDE3 inhibitors milrinone, amrinone, and levosimendan are able to modulate cyclic nucleotide regulation in hypothermic settings. Materials and methods The effect of PDE3 inhibitors were studied by using recombinant phosphodiesterase enzymes and inverted erythrocyte membranes at six different temperatures - 37°C, 34°C, 32°C, 28°C, 24°C, and 20°C- in order to evaluate the degree of enzymatic degradation, as well as measuring cellular efflux of both cAMP and cGMP. The resulting dose-response curves at every temperature were used to calculate IC50 and Ki values. Results Milrinone IC50 and Ki values for cGMP efflux were significantly lower at 24°C (IC50: 8,62 ± 2,69 µM) and 20°C (IC50: 7,35 ± 3,51 µM), compared to 37°C (IC50: 22,84 ± 1,52 µM). There were no significant changes in IC50 and Ki values for enzymatic breakdown of cAMP and cGMP. Conclusion Milrinone, amrinone and levosimendan, were all able to suppress enzymatic degradation and inhibit extrusion of cGMP and cAMP below 30°C. Our results show that these drugs have preserved effect on their target molecules during hypothermia, indicating that they could provide an important treatment option for hypothermia-induced cardiac dysfunction.